Compliances of Connectivity and Communication strategies of Wireless Sensor Network (WSN) over IoT - Srivastava, Atul Ranjan; Kushwaha, Vivek (International Journal of Computer Sciences and Engineering, 2019)
Wireless sensor networks (WSNs) enable new applications and require nonconventional paradigms for protocol design due to several constraints. Owing to the requirement for low device complexity together with low energy consumption (i.e., long network lifetime), a proper balance between communication and signal/data processing capabilities must be found. This motivates a huge effort in research activities, standardization process, and industrial investments on this field since the last decade. This survey paper aims at reporting an overview of WSNs technologies, main applications and standards, features in WSNs design, and evolutions with connections of Internet of things. The Internet of Things, or IoT, refers to the set of devices and systems that interconnect real-world sensors and actuators to the Internet. Emphasis is given to the IEEE 802.15.4 technology, which enables many applications of WSNs. Some example of performance characteristics of 802.15.4based networks are shown and discussed as a function of the size of the WSN and the data type to be exchanged among nodes.